Action of the gibberelin in seeds previous absorption of castor bean - Peixoto, Clovis Pereira; Sales, Franklim de Jesus Soares; Vieira, Elvis Lima; Passos, Adriana Rodrigues; dos Santos, Jamile Maria da Silva (Comunicata Scientiae, 2011)
A experiment was conducted in the Universidade Federal do Roconcavo da Bahia (UFRB), under greenhouse conditions, with the purpose of verify the action of liquid giberelin over the emergency of castor bean seedlings. Castor bean seeds from BRS 188 Paraguaçu cultivar were submerged for 3 hours in a solution of giberelic acid (GA3) on concentrations zero, 50, 100 and 150 μL L-1 and then planted in plastic trays, containing washed sand. An entirely random alignment was used with five treatments and five repetitions. Each experimental unit was formed by a tray, where were planted 25 seeds. The number of emerged seeds was daily registered. On the fifth day the percentage of emergency was calculated, and on the thirtieth day it was evaluated the measurement from the root to the aerial parts. The dry mass was, also, evaluated after three days in the greenhouse with artificial ventilation under 65 °C. The conclusion is that the gibberelin on the dose of 100 μL L-1 is the best treatment to the percentage of the first counting, index of emergency speed, emergency, length and dry mass of the root and aerial parts of castor beans plants.